THE ANALYSIS OF ISLAMIC ECONOMY IN THE CONSTITUTION OF INDONESIA - Hamidah, Siti; Bakri, Mochammad; Budiono, Abdul Rahmad; Winarno, Bambang (Faculty of Law, Universitas Brawijaya, 2017)
The development of Islamic Economy has been flourishing in the life of Indonesian people and brings impacts to several aspects of life, including in the field of law serving as the juridical basis. Indonesia is not an Islamic country. Instead, it is a constitutional country that believes in one Supreme God and protects all people to practice their religions. The sociological condition of the majority affects the formulation of law and constributes to the positive law which includes in it the issue on constitutional law. This paper analyzes the flexibility of Indonesian's constitution in adopting and providing spaces for Islamic Economy as well as becoming the foundation for Islamic economy to fulfill the need of the society. Firstly, the analysis was conducted using theoretical approach viewed from the persepctive of the correlation between the state and religion, and the theory on legal pluralism. Further, the 1945 Constitution of State of Republic of Indonesia (Undang-Undang Dasar Negara Republik Indonesia/UUD NRI 1945), was analyzed to trace the basis of Islamic economy and to develop Islamic economy based on the Indonesian's constitution.